Indigenous People as “Object-Matter” - Intan Permata Sari; Irwan Abdullah (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
The literary tendency to map and position indigenous people as passive objects can be seen in three domains: (1) a study that maps the identity of indigenous people as something “authentic”; (2) subordinated by dominant groups; and (3) vulnerable to change. This paper places indigenous people as the subject matter where the subject’s perspective is accommodated in understanding their ideas and choices of attitudes and ways of life. This paper aims to (1) answer the question of how the literature defines the identity of indigenous people; (2) showing the misconceptions built by various literatures in interpreting the identity of indigenous people; (3) showing that stereotypes about indigenous people as a construction of thought from those in power. The data source for this article comes from literature in the form of journal articles and books. Two things can be reflected from this study of indigenous people: 1) the identity of indigenous people has been defined unilaterally by other people (outsiders); 2) the tendency of the literature to place indigenous people as passive objects that are static, accepting fate and not contributing to civilization.